2017
DOI: 10.1021/acs.est.7b01009
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and Naturally Produced Brominated Phenols in Pet Blood and Pet Food in Japan

Abstract: Present study determined concentrations and residue patterns of bromophenols (BPhs) in whole blood samples of pet cats and pet dogs collected from veterinary hospitals in Japan. BPhs concentrations were higher in cat blood than in dog blood, with statistically insignificant differences (p = 0.07). Among the congeners, 2,4,6-tribromophenol (TBPh) constituted the majority of BPhs (>90%) detected in both species. Analysis of commercial pet food to estimate exposure routes showed that the most abundant congener in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…BDE-209 levels were similar to those previously reported , for human wristbands, but the DF was less than 50% in our dog tags. Interestingly, BDE-209 has been reported as one of the more abundant congeners in studies measuring levels in dog tissues. Although this is a major congener found in house dust, , it is also reportedly high in dry dog food. , It is possible the high levels of BDE-209 previously reported in dog tissues may be due to higher dietary exposure and thus not captured by the silicone dog tags, although it is also possible that exposure may be decreasing for PBDEs because they have now been phased out of production. In contrast, 2-ethylhexyl-2,3,4,5 tetrabromobenzoate (EH-TBB) and bis­(2-ethylhexyl)­tetrabromophthalate (BEH-TEBP) were the most abundant BFRs measured on the wristbands (GM = 140.2 and 105.7 ng/g, respectively) and dog tags (GM = 35.9 and 21.4 ng/g, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…BDE-209 levels were similar to those previously reported , for human wristbands, but the DF was less than 50% in our dog tags. Interestingly, BDE-209 has been reported as one of the more abundant congeners in studies measuring levels in dog tissues. Although this is a major congener found in house dust, , it is also reportedly high in dry dog food. , It is possible the high levels of BDE-209 previously reported in dog tissues may be due to higher dietary exposure and thus not captured by the silicone dog tags, although it is also possible that exposure may be decreasing for PBDEs because they have now been phased out of production. In contrast, 2-ethylhexyl-2,3,4,5 tetrabromobenzoate (EH-TBB) and bis­(2-ethylhexyl)­tetrabromophthalate (BEH-TEBP) were the most abundant BFRs measured on the wristbands (GM = 140.2 and 105.7 ng/g, respectively) and dog tags (GM = 35.9 and 21.4 ng/g, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…As an important representative group of water-soluble contaminants, bromophenols have well-known anthropogenic and natural sources. Bromophenols are also transformation products of polybrominated diphenyl ethers (PBDEs), MeO-PBDEs, OH-PBDEs, TBBPA, and 1,2-bis (2,4,6-tribromophenoxy) ethane. , Moreover, bromophenols have the potential to bind with estrogen receptors and the thyroid hormone transport protein transthyretin, which could result in endocrine-disrupting effects. , The phenolic hydroxyls of contaminants (e.g., TBBPA, triclosan, and bromophenols) are generally bonded with sulfate and/or glucoside groups without the activation processes in Phase I metabolism (e.g., hydroxylation process), directly forming sulfation , and diverse glycosylation conjugates in pumpkins, carrots, and rice seedlings. …”
Section: Introductionmentioning
confidence: 99%
“…Hydroxylated metabolites of these halogenated compounds have structural similarities of the natural thyroid hormones T 4 and T 3 [33, 37]. Analyses of cat blood serum from different parts of the world have shown high levels of PBDEs, higher than found in humans from the same area [12, 15, 18, 19, 22, 24]. The usage of PBDEs were introduced to the market just prior to the first cases of FHT were recorded [38].…”
Section: Endocrine Disrupting Chemicals In Catsmentioning
confidence: 99%
“…Both 2,4,6-TBP and 6-OH-BDE47 are natural compounds formed by marine plants and may enter the food chain via sea food [45, 46]. Further, it was shown that cat liver microsomes were unable to form the 2,4,6-TBP metabolite from the parent PBDEs by incubation, indicating that cat food may be the source of the 2,4,6-TBP found in serum [24]. These phenolic compounds have a high binding affinity to the transport protein TTR and can competitively replace the natural ligand to be transported to its target tissue [47].…”
Section: Endocrine Disrupting Chemicals In Catsmentioning
confidence: 99%